PEMILIHAN KEPALA DESA GARECCING KECAMATAN SINJAI SELATAN KABUPATEN SINJAI PERSPEKTIF SIYASAH SYAR’IYYAH - Lestari, Firda Ayu; Rahmiati, Rahmiati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The election of village heads is a process of selecting leaders democratically at the lowest level of government and is carried out directly. The study aims to find out how the selection process for the Head of Gareccing Village in the perspective of siyasah syar'iyyah using qualitative types of research, through juridical and normative syar'i approaches. The selection process for the Head of Gareccing Village starts from the stages of forming an election committee, registering candidates, voting, determining selected candidates, and inaugurating the elected village head, and the process has been carried out in accordance with applicable regulations. Political contestation that takes place every 6 (six) years is not colored by dirty practices, such as intimidation and money politics, so that public participation is quite high. Although in the history of Islamic constitutionality there has never been an example of a direct election mechanism such as the election of the Head of Gareccing Village, it does not mean that the mechanism is contrary to the principles of Islamic teachings. Because, from the time the Prophet Muhammad saw to his companions, there was no uniform mechanism in selecting leaders.